Positive Parenting Training on the Quality of Maternal Care with Early Childhood at SPS Teratai - Anggreni, Ni Wayan Yuli; Swasti, Idei Khurnia; Putri, Putu Riana Artyanti; Winayanti, Ratna Devy; Pramana, Ida Bagus Gde Yoga; Apsari, Ayu Rahmadita (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Good quality care can mean that parents are able to provide care that suits their child's needs. Good quality in parenting is related to parents' knowledge about positive parenting. Positive parenting is a parenting style that balances warmth and appreciation with the rules and discipline that parents apply to their children. This research aims to determine the effect of positive parenting training on the quality of care for mothers of early childhood at SPS Teratai. The subjects of this research were mothers of early childhood children aged 2-6 years at SPS Teratai. The measuring tool used is the parenting quality scale from Efnita (2014). The results of the research show that the statistical test using the Wilcoxon Signed Rank Test using the SPSS 21.00 for Windows application shows a probability value of 0.027 (p<0.05). This shows that there is a change in the quality of parenting between the groups before and after positive parenting training. The results of the FGD also showed that participants learned about positive parenting which focuses on reducing negative parental behavior in caring for children, increasing attention to positive behavior in children and establishing empathetic closeness to children, carrying out more positive discipline so that they do not use violence either physically. verbal and emotional.Kualitas pengasuhan yang baik dapat bermakna bahwa orangtua mampu memberikan pengasuhan yang sesuai dengan kebutuhan dari anaknya. Kualitas yang baik dalam pengasuhan berkaitan dengan pengetahuan orangtua tentang pengasuhan yang positif. Pengasuhan positif adalah pola asuh yang menyeimbangkan antara kehangatan serta pengahargaan dengan aturan dan disiplin yang diterapkan orangtua kepada anaknya. Penelitian ini bertujuan untuk mengetahui pengaruh pelatihan pengasuhan positif terhadap kualitas pengasuhan ibu dari anak usia dini di SPS Teratai. Subjek penelitian ini adalah ibu dari anak usia dini yang berusia 2-6 tahun di SPS Teratai. Alat ukur yang dipakai adalah skala kualitas pengasuhan dari Efnita (2014). Hasil penelitian menunjukkan bahwa dari uji statistik dengan uji beda Wilcoxon Signed Rank Test dengan bantuan aplikasi SPSS 21.00 for windows menunjukkan nilai probabilitas 0,027 (p<0,05). Hal ini menunjukkan bahwa terdapat perubahan kualitas pengasuhan antara kelompok sebelum dan sesudah pelatihan pengasuhan positif. Hasil FGD juga menunjukkan bahwa peserta belajar tentang pengasuhan positif yang berfokus untuk mengurangi perilaku negatif orangtua dalam melakukan pengasuhan kepada anak, meningkatkan perhatian pada perilaku positif pada anak dan menjalin kedekatan yang penuh empati kepada anak, melakukan disiplin yang lebih positif sehingga tidak menggunakan kekerasan baik secara verbal maupun emosional.